Minimal Change Nephrotic Syndrome with Acute Kidney Injury after the Administration of Pfizer-BioNTech COVID-19 Vaccine - Erdinc Gulumsek; Dilan Damla Ozturk; Huseyin Ali Ozturk; Tayyibe Saler; Kivilcim Eren Erdogan; Ahmed Muhammad Bashir; Hilmi Erdem Sumbul (Case Reports in Infectious Diseases)
Nephrotic syndrome progresses with various metabolic disturbances, such as proteinuria over 3.5 grams in 24 hours, hypoalbuminemia, and hypercoagulability. Patients usually complain about diffuse edema throughout the body, which is secondary to hypoalbuminemia. It has many primary and secondary causes. Patients may require a renal biopsy to confirm the diagnosis. Besides, many secondary causes of nephrotic syndrome should be examined and excluded. Although many vaccines were developed due to the COVID-19, many side effects are still reported because of the Pfizer-BioNTech COVID-19 vaccine (COVID-19 mRNA and BNT162b2), which is widely used in Turkey. This study examines a case of nephrotic syndrome with acute renal injury after Pfizer-BioNTech vaccine.